Association of risk factors of carcinoma cervix with abnormal pap results among women attending a tertiary care hospital of jharkhand: A cross sectional study - Kumar, Abhishek; Shikha, Swati; Kashyap, Vivek (Asian Journal of Medical Sciences, 2021)
Background: Cervical cancer has become a vital cause of cancer mortality among women worldwide. It is the fifth most common cancer overall and second most common cancer among women worldwide. Aims and Objectives: To assess the frequency of established risk factors of cervical cancer among study subjects and to find out the association between socio demographic variables and risk factors with results of pap smear test. Materials and Methods: Hospital based cross sectional study was conducted in Pathology department of Rajendra Institute of medical sciences, Ranchi for 3 months (September – November 2017) on total of 106 women who gave consent. Results: All the women (n=106) were married, 68 out of 106 (64.2%) were Hindus, 57 out of 106 (53.8%) were non Tribals 60.4% were from urban area and most of them 62 out of 106 (58.49%) were housewives. Amongst risk factors, 69 out of 106(65.09%) had their first sexual intercourse before 18 years of age, only 11 out of 106 (10.4%) were addicted to smoking and 42 out of 106 (39.62%) had past history of STIs. Educational status and Socio economic status was found to be significantly associated with abnormal pap smear results with p value <0.05. Conclusion: Most of the women were from non tribal ethnicity and urban background and illiterate with the mean age of 37.9± 10.56 years. Educational status and Socio economic status were significantly associated with abnormal Pap results.